Peran Harga Dan Promosi Mendukung Loyalitas Melalui Kepuasan Pada UMKM Laundry “Harfia" Jakarta Pusat - Harries Madiistriyatno (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research aims to examine the role of prices and promotions in supporting customer loyalty through satisfaction at HARFIA Laundry MSMEs. Using a qualitative approach, this research collects data through in-depth interviews with customers and business owners, as well as direct observation in the field. The research results show that competitive prices and effective promotional strategies play an important role in increasing customer satisfaction. This satisfaction, in turn, contributes significantly to customer loyalty. Customers who are satisfied with the prices offered and attractive promotions tend to return to using this laundry service and recommend it to others. This research concludes that integration between appropriate pricing and strategic promotions is the key to maintaining and increasing customer loyalty to HARFIA Laundry MSMEs.